FACILE IN VITRO GLASS SLIDE LIGHT MICROSCOPY METHOD USING TETRACYCLINE TO VISUALIZE A REPETITIVE PATTERN IN AERIAL PLANT ROOT TIPS FILAMENTOUS NETWORK - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2021)
The main purpose of this manuscript is to introduce a facile light microscopy methodology to visualize plant roots filaments. In a previous manuscript in vitro experiments on freshly plucked human hair roots documented the commonly used antibiotic Tetracycline (TE) deleterious effect on soft tissue, severe enough to allow for visualization of an underlying filamentous skeleton. In this manuscript, TE was also evaluated in a similar fashion of in vitro experiments, this time aerial plant roots were immersed in liquid Tetracycline. Images and video recordings are presented where plant aerial root tissue cells appeared to interact with Tetracycline, thus allowing for exposure of an underlying filamentous network. These filaments were documented undergoing biosorption of Tetracycline, thus indicating a probable keratin base. It is emphasized that a literature search showed similar, albeit visually different displays of roots filaments obtained by using a Scanning Electron Microscopy. The method herein introduced could be an adjunct to existing established methodology in root function research. Two salient advantages are identified, firstly that the essential minimal material and equipment is limited to a light microscope, glass slides, chosen biological material, water and powder Tetracycline. Secondly, the speed in obtaining results would offer researchers a preliminary or perhaps a final correct conclusion.